2006
DOI: 10.2174/157339606775518377
|View full text |Cite
|
Sign up to set email alerts
|

Knemometry for Assessment of Growth Suppressive Effects of Exogenous Glucocorticoids

Abstract: Exogenous glucocorticoids are commonly used in the treatment of various conditions including asthma, rhinitis, and a range of renal, gastrointestinal and malignant diseases in children. Glucocorticoid treatment has numerous systemic side effects beside the beneficial effects. An important and well described side effect is growth suppression. Knemometry, i.e. measurement of the lower leg length, is a well established method for assessment of short term growth. The present article reviews the role of knemometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The two studies were designed to investigate a wide range of systemic effects during glucocorticoid treatment, including short-term growth of the lower leg assessed by knemometry [15]. The power calculations were based on previous knemometry data and showed that to be able to detect a 50% reduction in lower leg growth rate with 80% probability, 16 children had to complete the study [16, 17].…”
Section: Methodsmentioning
confidence: 99%
“…The two studies were designed to investigate a wide range of systemic effects during glucocorticoid treatment, including short-term growth of the lower leg assessed by knemometry [15]. The power calculations were based on previous knemometry data and showed that to be able to detect a 50% reduction in lower leg growth rate with 80% probability, 16 children had to complete the study [16, 17].…”
Section: Methodsmentioning
confidence: 99%